Pengaruh Iklim Organisasi Dan Motivasi Kerja Terhadap Organizational Citizenship Behavior (Perilaku Keanggotaan Organisasi) Guru SMA Swasta Buddhis Se-DKI Jakarta - Manggala Wiriya Tantra; Eliana Sari; Francis Tantri (Jurnal Ilmiah Wahana Pendidikan, 2018)
This study aims to determine the effect of (1) organizational climate, (2) work motivation, (3) organizational citizenship behavior of high school teachers in the capital city of Jakarta. In data analysis, this study uses causal survey method using Path Analysis Technicque. This study used a sample of 138 teachers in 7 Buddhist secondary schools in the capital city of Jakarta who were selected using the Slovin formula. The results revealed that: first, there was a positive effect between the organizational climate and organizational citizenship behavior of teachers in schools. This means that an increase in the organizational climate results in an increase in teacher's organizational citizenship behavior. Second, there is a positive effect between work motivation and organizational citizenship behavior of teachers in schools. This means that increasing work motivation results in an increase in teacher's organizational citizenship behavior. Third, there is a positive effect between the organizational climate and the work motivation of teachers in schools. This means that an increase in the organizational climate has resulted in an increase in teacher's work motivation.